Identifying Students’ Problems in Speaking English - Fitri, Mainar; Huda, Fadilla Azelya; Nurzena, Nurzena (Journal of English and Arabic Language Teaching, 2024)
The purpose of this research was to describe students’ dominant problems in speaking English at one of state Islamic senior high school in Pekanbaru, Riau Province; Indonesia. This research was descriptive quantitative research. The population of this research was 395 from 12 classes and the researcher took the sample by using purposive sampling technique with total of samples were 60 students. The instrument used in this research was a documentation.  The researcher analyzed the data by using total score. Based on the result of the research, it was found that the students’ dominant problems in speaking English was fluency with the total score was 187. The researcher concludes that fluency is the most dominant problem faced by the students in speaking English.